2013
DOI: 10.18869/acadpub.rmm.1.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association Hind III Polymorphism of Lipoprotein Lipase gene on the risk of coronary artery disease

Abstract: Background: Coronary artery disease (CAD) is one of the leading causes of death and disability around the world. Interaction between genetic and environmental factors determines susceptibility of an individual to develop coronary artery disease. Lipoprotein lipase (LPL) plays an important role in the metabolism of HDL-C (High Density Lipoprotein Cholesterol), LDL-C (Low Density Lipoprotein Cholesterol) and triglycerides (TG). Dysfunction of LPL as a result of genetic variants of lipoprotein lipase gene is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…According to our statistical analysis, the H+H+ LPL-Hind lll polymorphism was the strongest genetic marker of susceptibility to severe hypertriglyceridemia, which was similar to the results of other studies [17]. The effect of the LPL-Hind III polymorphism on lipid parameters has not demonstrated the same consistency across other populations.…”
Section: Discussionsupporting
confidence: 82%
“…According to our statistical analysis, the H+H+ LPL-Hind lll polymorphism was the strongest genetic marker of susceptibility to severe hypertriglyceridemia, which was similar to the results of other studies [17]. The effect of the LPL-Hind III polymorphism on lipid parameters has not demonstrated the same consistency across other populations.…”
Section: Discussionsupporting
confidence: 82%
“…In a more recent study, it was established that the presence of homozygous genotype for the common allele (H+/H+) of the LPL gene is a risk factor for a first episode of myocardial infarction 65 . Conversely, studies by Imeni et al 78 in an Iranian population, showed no statistically significant associations between CAD and genotypic distributions of HindIII polymorphism. 80 .…”
mentioning
confidence: 70%
“…Conversely, studies by Imeni et al . 78 in an Iranian population, showed no statistically significant associations between CAD and genotypic distributions of HindIII polymorphism.…”
Section: Hindiii (Rs320) Polymorphismmentioning
confidence: 82%